Attuning to the World: The Diachronic Constitution of the Extended Conscious Mind - Kirchhoff, Michael D.; Kiverstein, Julian (Frontiers in Psychology, 2020)
It is a near consensus among materialist philosophers of mind that consciousness must somehow be constituted by internal neural processes, even if we remain unsure quite how this works. Even friends of the extended mind theory have argued that when it comes to the material substrate of conscious experience, the boundary of skin and skull is likely to prove somehow to be privileged. Such arguments have, however, typically conceived of the constitution of consciousness in synchronic terms, making a firm separation between proximate mechanisms and their ultimate causes. We argue that the processes involved in the constitution of some conscious experiences are diachronic, not synchronic. We focus on what we call phenomenal attunement in this paper—the feeling of being at home in a familiar, culturally constructed environment. Such a feeling is missing in cases of culture shock. Phenomenal attunement is a structure of our conscious experience of the world that is ubiquitous and taken for granted. We will argue that it is constituted by cycles of embodied and world-involving engagement whose dynamics are constrained by cultural practices. Thus, it follows that an essential structure of the conscious mind, the absence of which profoundly transforms conscious experience, is extended.